PREVALENCE OF ANTI-HCV, HBSAG, HIV AMONG MULTI-TRANSFUSED THALASSEMIC INDIVIDUALS AND THEIR SOCIO-ECONOMIC BACKGROUND IN EASTERN INDIA - Biswas, Aritra; Sarkar, Kahini; Firdaus, Rushna; Saha, Kallol; Gupta, Debanjali; Ghosh, Monika; Chowdhury, Prosanto; Bhattacharyya, Debmalya; Bhattacharya, Maitreyee; Sadhukhan, Provash Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The objective was to study the serological prevalence of post-transfusion transmitted infections such as hepatitis C virus (HCV), hepatitis B virus (HBV), and HIV among multi-transfused thalassemic individuals of the Eastern India and the socio and financial difficulties faced by them. Methods: The study was carried out from January 2012 until December 2014 involving 1711 thalassemic major individuals. Blood serum was collected from each patient to perform ELISA for the detection of HBV and HCV seroprevalence. HIV seropositivity along with their hematological and liver function parameters were obtained from the transfusion centers and the host institutions. Other socio-economic conditions were obtained by predesigned proforma of the questionnaire. Results: 67.9% males and 32.1% females were present in our study population of which 75% were from rural area. The mean hemoglobin was found to be lower, whereas mean ferritin, bilirubin, and liver enzymes were much higher than the normal range. Only a handful of 19.76% of the fathers of thalassemic individuals had secondary education. 263 families (15.37%) were familiar with the chances of transfusion-transmitted infections (TTIs). The dominant TTI found within the population was HCV with 18.70% prevalence followed by HIV (3.74%) and HBV (3.33%). 82.93% of the affected families suffered poverty with a meager monthly income within Rs. 5000 fighting against high costs of transfusion and related treatments. Conclusion: Our study reflects the different socio-economic and psychological burdens faced by the thalassemia patients and their families. The high rate of TTIs highlights the need for stringent screening of blood or blood products before administration. Keywords: Thalassemia, Socio-economic, Transfusion-transmitted infections, Hepatitis C virus, Hepatitis B virus, HIV.